The Correlation Between Sentence Patterns Mastery And Translating Ability - Dhian Marita Sari (Jurnal Ilmiah Wahana Pendidikan, 2022)
The translation is an essential component of teaching. It assists students in understanding the relationship between languages and develops skills required for all language studies. The majority of non-English majors in college have many challenges to interpret English translation. The study is intended to investigate the students’ sentence pattern mastery, their translation abilities, and the correlation between both variables. The study used a quantitative correlational approach. The population of the study consisted of 175 Ahmad Dahlan University English Education Study Program third-semester students. There were 122 students in the sample. The sentence pattern test and the translation test were used to collect data. Pearson’s Product moment Formula was used to analyze the collected data. As shown in the findings of this study, students' sentence pattern mastery and translating ability were categorized as moderate. The correlation coefficient between students' sentence pattern mastery and translation ability was 0.464. As a result, it was concluded that the student's mastery of sentence patterns contributed significantly to their translation ability. The better one attains sentence patterns, the better one's ability to translate. It can be stated that those who want to improve their translation skills should learn sentence patterns.